Limited overlapping roles of P15(INK4b) and P18(INK4c) cell cycle inhibitors in proliferation and tumorigenesis - Latres, Esther (Oxford University Press, 2000)
Entry of quiescent cells into the cell cycle is driven by the cyclin D-dependent kinases Cdk4 and Cdk6. These kinases are negatively regulated by the INK4 cell cycle inhibitors. We report the generation of mice defective in P15(INK4b) and P18(INK4c). Ablation of these genes, either alone or in combination, does not abrogate cell contact inhibition or senescence of mouse embryo fibroblasts in culture. However, loss of P15(INK4b), but not of P18(INK4c), confers proliferative advantage to these cells and makes them more sensitive to transformation by H-ras oncogenes. In vivo, ablation of P15(INK4b) and P18(INK4c) genes results in lymphoproliferative disorders and tumor formation. Mice lacking P18(INK4c) have deregulated epithelial cell growth leading to the formation of cysts, mostly in the cortical region of the kidneys and the mammary epithelium. Loss of both P15(INK4b) and P18(INK4c) does not result in significantly distinct phenotypic manifestations except for the appearance of cysts in additional tissues. These results indicate that P15(INK4b) and P18(IKN4c) are tumor suppressor proteins that act in different cellular lineages and/or pathways with limited compensatory roles.